Unmet long-term care needs and their association with health-related quality of life among Chinese oldest-old population - Jiajun Qiao; Yiwei Qiao; Jialong Tan; Nuo Chen; Nan Peng; Zongfu Mao; Yali Zhao; Chen Chen; Yao Yao (Health and Quality of Life Outcomes)
Abstract Background Entering the age of 80 or 100, individuals’ functional decline and the need for assistance in daily activities increase dramatically, resulting in an inevitable increase in unmet long-term care (LTC) needs. Understanding unmet LTC needs in late life and their association with quality of life is essential for effective health planning and resource allocation. We aim to estimate the prevalence of unmet needs for LTC and the association of unmet needs for LTC and Health-related Quality of life (HRQOL), among the Chinese oldest-old population. Methods Data were drawn from the 2017 China Hainan Centenarian Cohort Study. All centenarians and a representative sample of individuals aged between 80 and 99 years old in Hainan province, China were included. Self-perceived unmet LTC needs were reported by the respondents. EQ-5D score was calculated from EQ-5D-3L questionnaire to measure HRQOL in this study. We conducted Tobit regression and the Ordered Probit Model to examine the cross-sectional associations between unmet needs for LTC and HRQOL. Results 1,444 respondents (mean age 95.75 years [SD 9.13]) were included. The prevalence of unmet LTC needs was 32.69%, and it was higher in rural residents and people with economic deprivation. The results showed that oldest-old individuals with unmet needs for LTC reported lower QALY scores (β=-0.04, p < 0.01). In addition, Unmet LTC needs were significantly correlated with poorer outcomes in mobility (β = 0.18, p < 0.05), self-care (β = 0.19, p < 0.05), pain or discomfort (β = 0.27, p < 0.01), and anxiety or depression (β = 0.09, p < 0.01). Conclusions The prevalence of unmet LTC needs was higher in China than its counterpart in high-income countries, especially among those with socio-economic deprivation. Individuals with unmet LTC needs experience lower quality-adjusted life years (QALYs) and higher levels of disabilities across multiple dimensions of health, including mobility, usual activities, self-care, pain/discomfort and depression/anxiety. These findings underscore the importance of addressing unmet LTC needs to improve the overall health outcomes and quality of life for the oldest-old population.